Case Report: A Novel Homozygous Variant Identified in a Chinese Patient With Benign Recurrent Intrahepatic Cholestasis-Type 1 - Chen, Huayu; Wu, Dongbo; Jiang, Wei; Lei, Ting; Lu, Changli; Zhou, Taoyou (Frontiers in Medicine, 2021)
Benign Rrecurrent Iintrahepatic cCholestasis (BRIC) is a rare hereditary cholestatic liver disorder. Accurate diagnosis and timely interventions are important in determining outcomes. Besides clinical and pathologic diagnosis, genetic study of BRIC remains limited. Here, we report a young man enduring recurrent jaundice and severe pruritus for 15- years. The increased level of direct bilirubin was the main biochemical abnormality, and the work-up for common causes of jaundice were unremarkable. Liver biopsy showed extensive cholestasis of hepatocytes in zone 3. The novel homozygous variant including c.1817T>C and p.I606T was detected on his ATP8B1gene. The patient was finally diagnosed with BRIC-1. His symptoms were relieved, and liver function tests returned to normal after taking ursodeoxycholic acid. Our This case provides a different perspective to the methodology employed while when dealing with cases of jaundice and helping diagnose rare diseases.